Social Determinants of Adolescent Health Culture: a Systematic Approach to Research in the Context of Modern Challenges - N. V. Biryukova; R. A. Khalfin; V. V. Madyanova (Здоровье мегаполиса)
Background. Improving the culture of health and the formation of the need to preserve and maintain health is a complex healthcare problem, since it can be associated with a wide range of social determinants, which include, but are not limited to, family upbringing, access to education, economic conditions, socio-demographic characteristics and the influence of the information environment. New challenges faced by modern society, including the rapid growth of digital technologies, changing social norms and environmental degradation, significantly influence the approaches to the formation of a culture of health and maintaining a health-saving lifestyle among young people.The purpose of the study was to identify the social determinants that have the greatest impact on the formation of health culture among adolescents aged 15-18 years.Materials and methods. In the course of the work, a theoretical analysis of scientific literature studying the influence of social determinants on the culture of adolescent health was carried out. A study using the survey method was conducted with participation of 15-18 year-olds studying at the Pre-University of I.M. Sechenov First Moscow State Medical University and similar educational institutions of Bryansk, Magadan, Petropavlovsk-Kamchatsky, Saratov, and Donetsk.Results. The study showed that family environment, educational system and socio-economic status have a significant impact on the development of adolescent health culture. The most common factors that have the most negative impact (binge eating, simultaneous eating and reading, abuse of salt, sweets and spices, sleep disorders), as well as less common (use of toxic drugs, procrastination, computer games, physical and emotional overload and sport injuries) were identified. One third of the surveyed schoolchildren reported about a combination of several health risks.Conclusion. The study increases knowledge about social determinants that are key to understanding of the culture and health of adolescents. The analysis focused on critical aspects such as the social environment and its impact on health, individual attitudes to health, and behavioral risks relevant to the psychophysical development of adolescents. Upon the results of the conducted study, a “Database of monitoring of sociocultural factors of health and healthcare” was created.